2012
DOI: 10.5539/jfr.v1n2p13
|View full text |Cite
|
Sign up to set email alerts
|

Nudging Customers towards Healthier Choices: An Intervention in the University Canteen

Abstract: The notion of nudge effects was investigated in two field experiments which focused on influencing customers' purchases by manipulating the location and availability of food in a University canteen setting. Study 1 manipulated the location of fruit and confectionary. Study 2 restricted the types of bread (i.e. brown only not white) that customers could choose for their sandwiches. The results of the Study1 showed that the fruit sales increased when positioned away from the checkouts. The majority of interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In all the stores considered, unhealthy snacks were removed from all the checkouts of each store and were displayed away from that area on a sideboard, as tested in a previous study (Chapman and Ogden, 2012). At the checkouts, they were all replaced by a selection of healthy products (mix of fresh fruit, dried fruit, dried fruit bars, nuts and smoothies).…”
Section: Procedures -The Development Of the Healthy Checkoutmentioning
confidence: 99%
“…In all the stores considered, unhealthy snacks were removed from all the checkouts of each store and were displayed away from that area on a sideboard, as tested in a previous study (Chapman and Ogden, 2012). At the checkouts, they were all replaced by a selection of healthy products (mix of fresh fruit, dried fruit, dried fruit bars, nuts and smoothies).…”
Section: Procedures -The Development Of the Healthy Checkoutmentioning
confidence: 99%
“…This association was significant in eight studies, with inconsistent evidence of significance found in three studies. One methodologically weak study 69 observed that checkout placement was associated with a significant decrease in sales of promoted foods.…”
Section: Resultsmentioning
confidence: 99%
“…Salad bar purchases increased a Moderate Van Gestel et al [ 56 ] 2017 The Netherlands Unhealthy snacks at the check-out counter were replaced by healthy snacks Pre-post 1 small food store > 1 week & ≤ 1 month Small food store N/A Purchases of healthy snacks Point of sale system 6. Healthy snack purchases increased a Moderate Chapman et al [ 57 ], study 1 2012 UK Confectionery was removed from check-out counters and replaced by fruit Pre-post 1 cafeteria ≤ 1 week University cafeteria N/A Purchases of fruit; Purchases of confectionery Point of sale system 7a. Healthy fruit purchases decreased a 7b.…”
Section: Methodsmentioning
confidence: 99%